Prognostic Impact of Potentially Curative Resection for Synchronous Peritoneal Carcinomatosis with Lavage Cytology Positivity in Colorectal Cancer: A Retrospective Observational Study - Kentaro Sato; Shimpei Matsui; Tomohiro Chiba; Tatsuki Noguchi; Takashi Sakamoto; Toshiki Mukai; Tomohiro Yamaguchi; Takashi Akiyoshi; Yosuke Fukunaga (Journal of the Anus, Rectum and Colon)
Objectives: Although curative resection for synchronous peritoneal carcinomatosis has been reported to improve prognosis, cases with positive intraoperative lavage cytology have not been reported. In this study, we investigated the prognostic value of potentially curative resection based on colorectal cancer and lavage cytology positivity in patients with synchronous peritoneal carcinomatosis. Methods: We retrospectively evaluated 72 patients who underwent intraoperative lavage cytology and one-stage potentially curative resection of primary and metastatic lesions (lavage cytology-positive, n = 21; lavage cytology-negative, n = 51) between July 2004 and December 2019. We compared the 5-year overall survival and 3-year recurrence rates between the lavage cytology-positive and lavage cytology-negative groups. Results: No significant differences were observed in the 5-year overall survival (48.2% vs. 45.5%, P = 0.924) or 3-year recurrence rates (74.5% vs. 62%, P = 0.143) between the two groups. Univariate analysis for 3-year recurrence revealed that lavage cytology-positive status was not an explanatory variable (hazard ratio: 1.552, 95% confidence interval: 0.83-2.902, P = 0.169). Multivariate analysis identified colon cancer as an independent risk factor of recurrence. Conclusions: In resectable cases, the resection of synchronous peritoneal carcinomatosis from colorectal cancer can be considered even if intraoperative lavage cytology is positive.